Memahami Larangan Kawin Beda Agama di Indonesia (Kajian Filsafat Hukum Islam) - Wijayati, Mufliha (Istinbath : Jurnal Hukum, 2022)
This article explains the ratio legis of prohibition of interfaith marriage in Indonesia. Indonesia has indirectly prohibited interfaith marriage through the marriage law, the Compilation of Islamic Law, and the fatwa of the Indonesian ulama Council (MUI). The research data was obtained from a literature review of theworks of scholars who discussed the wisdom prohibiting interfaith marriage. Althought there are differences of opinion and interpretation in figh discourse regarding the legal statur of interfaith marriage, depending on personal and political situations, this article argues that the state still priotitizes to choose a life partner, which is the argument of advocates of the legality of interfaith marriage. This prohibition is based on views related to personal (theological) and communal (political) beliefs, that the purpose of marriage is to achieves a happy, peaceful, and loving family which is difficult to achieve in interfaith marriage. This overarching narrative is still maintained, although efforts to amend it are made in vatious ways